Quality of Health Services in the First Level Health Facilities and the Role of Quality and Cost Control Team in Lampung Province - Asep Sukohar; Arli Suryawinata; Aulian Mediansyah (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
Background: The National Health Insurance/Jaminan Kesehatan Nasional (JKN) program is a public health protection guarantee held by the Social Securite Management Agency/Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS) to ensure that all Indonesians receive comprehensive, fair, and equitable health care benefits. The health services are provided using a tiered service system with the first stage in the First Level Health Facilities/Fasilitas Kesehatan Tingkat Pertama (FKTP) acting as a gatekeeper. In conducting these duties, they must always be maintained with good cost-efficiency to be able to provide optimal health service quality. The audit function is imposed by the Quality and Cost Control Team/Tim Kendali Mutu Kendali Biaya (TKMKB) which partners with BPJS. Until now, various efforts to improve the quality of services continue to be developed, one of which is the capitation-based service commitment/Kapitasi Berbasis Komitmen Pelayanan (KBK) payment method. Quality of health services in FKTP can be seen through the high number of FKTP that are affected by the capitation-based service commitment (FKTP KBK-K) payment. Additionally, the high number of FKTP KBK-K can also be a measure of the success of the quality and cost control program implemented by the regional TKMKB. Objective: To assess the quality of health services in FKTP and the TKMKB performance of Lampung Province. Methods: This research was a descriptive-analytic study using data from the BPJS report of Lampung Province and TKMKB in the first and second quarters of 2019. Results: There was an increase in the number of FKTP KBK-K in Lampung Province in the second quarter of 2019, not achieving the minimum contact number, with a low ratio of Prolanis Routine Participants Visiting/Rasio Peserta Prolanis Rutin Berkunjung (RPPRB) especially at the FKTP non-Primary Health Care Centers (non-Puskesmas) in Lampung Province. Conclusion: An increase in the number of FKTP KBK-K that is not accompanied by an increase in the clinical ability of primary health care providers (such as family doctors/primary care doctors) can reflect suboptimal health services in FKTP. Also, this can further serve as a benchmark that the performance of the provincial TKMKB is not yet optimal.